El pasado en el presente: primitivismo en la obra de Eduardo Ramírez-Villamizar, Edgar Negret y Jorge Riveros (2020)
During the 20th Century, Colombian and Latin American Art History reviewed the work of artists Edgar Negret, Eduardo Ramírez-Villamizar and Jorge Riveros focusing on the abstraction and the important changes that their geometric language generated in the Colombian art scene. But, despite being a recurring theme in their works, their titles and their discourse, the interest of these artists in pre-Columbian art has been treated in a marginal way and even naming them as primitivists has been completely omitted, despite following the same guidelines as many primitivist artists, such as Picasso, Pollock or Torres-García. This work then seeks to analyze the way in which Negret, Ramírez-Villamizar and Riveros dealt with pre-Columbian artefacts and how this legacy is evident in their work, in order to understand their approach to primitivism. Proving that through geometry and different materials, Colombian primitivist seek to reconnect the pre-Columbian past with the modern present..